2015
DOI: 10.13075/mp.5893.00231
|View full text |Cite
|
Sign up to set email alerts
|

Fibers as carriers of microbial particles

Abstract: StreszczenieWstęp: Celem badania była ocena możliwości transportu cząstek biologicznych przez naturalne, syntetyczne i sztuczne włókna. Materiał i metody: Równoczesne pobieranie próbek pyłu osiadłego i aerozolu włóknistego przeprowadzono w 3 zakładach przetwarzających naturalne (bawełna, jedwab, len, konopie), syntetyczne (poliakrylonitrylowe, poliamidowe, polipropylenowe, poliestrowe) i sztuczne (wiskozowe) materiały włókniste; w 2 stajniach, gdzie hodowano konie i owce; w 4 domach, w których mieszkały psy i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Also, it can be observed in Figure 10, the structure of a single fiber of natural origin. In the case of natural fibers, with a lose arrangement, the rough, lamellar surface structure means that they are able to transport significant amounts of material, including microbial origin [66]. Computer enlargement of the image of the same fragment of the sample, showing the tested fibers, allows to detect the presence of dust particles and microbiological contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can be observed in Figure 10, the structure of a single fiber of natural origin. In the case of natural fibers, with a lose arrangement, the rough, lamellar surface structure means that they are able to transport significant amounts of material, including microbial origin [66]. Computer enlargement of the image of the same fragment of the sample, showing the tested fibers, allows to detect the presence of dust particles and microbiological contamination.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there are no noticeable differences in the state of conservation between the white and black fibers (from the manually embroidered model), both of which are in very good state of conservation. According to the literature on the subject [66,70,71] and the conducted research, it can be stated that the most common fungi found on the tested material (folk costume) and cellulose textiles (cotton, linen) include different species of Aspergillus, Penicillium, Alternaria, Botrytis, Chaetomium, etc. [70].…”
Section: Resultsmentioning
confidence: 99%
“…The suspicion of carcinogenic effects of mineral fibers in humans is mainly due to the similarity of their physical properties to the properties of asbestos fibers (similar fiber dimensions, a possibility of penetration into the respiratory system, and an ability to form free radicals). The basic differences between synthetic mineral fibers and asbestos are that mineral fibers are an amorphous synthetic material, resulting from the transformation of natural structures, and asbestos are naturally occurring fibers with a crystalline structure that allows the fibers to break along the crystalline planes and, as a result, creates fibers with diameters of 4 nm, which are easily transferred to the alveoli [6][7][8][9][10][11][12][13]. Moreover, MMVFs differ from asbestos fibers in their ability to produce fine dust, as well as in brittleness.…”
Section: Identification Of the Main Occupational Hazards Posed By Minmentioning
confidence: 99%
“…Textile goods themselves are to various degrees subject to biodestruction, resulting from the activity of microbiota [1]. Textiles of diverse composition for different uses may serve as the media conducive to the development of various microorganisms that produce mycotoxins which hit the airways [2]. Inhaling such products of microbiota in apartments, office facilities (curtains, wallpapers) or workplaces carries the risk of serious complications in the lungs.…”
Section: Introductionmentioning
confidence: 99%